2011
DOI: 10.1007/s00262-011-1064-9
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 (PGE2) suppresses natural killer cell function primarily through the PGE2 receptor EP4

Abstract: The COX-2 product prostaglandin E2 (PGE2) contributes to the high metastatic capacity of breast tumors. Our published data indicate that inhibiting either PGE2 production or PGE2-mediated signaling through the PGE2 receptor EP4 reduces metastasis by a mechanism that requires Natural Killer (NK) cells. It is known that NK cell function is compromised by PGE2, but very little is known about the mechanism by which PGE2 affects NK effector activity. We now report the direct effects of PGE2 on the NK cell. Endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 22 publications
2
121
0
Order By: Relevance
“…Considerable research has reported that NK cells express all PGE2 EP receptors and that PGE2 acts on NK cells through the EP2 and/or EP4 receptor subtypes, [73][74][75] which are known to be powerful activators of the adenylate cyclase system. 70 Since the adenylate cyclase system is involved in inhibiting killing by NK cells and inducing the CD94/NKG2A inhibitory NK receptor following PGE2 signaling, 76 it is not surprising that PGE2 has an inhibitory effect on NK cell function.…”
Section: 68mentioning
confidence: 99%
“…Considerable research has reported that NK cells express all PGE2 EP receptors and that PGE2 acts on NK cells through the EP2 and/or EP4 receptor subtypes, [73][74][75] which are known to be powerful activators of the adenylate cyclase system. 70 Since the adenylate cyclase system is involved in inhibiting killing by NK cells and inducing the CD94/NKG2A inhibitory NK receptor following PGE2 signaling, 76 it is not surprising that PGE2 has an inhibitory effect on NK cell function.…”
Section: 68mentioning
confidence: 99%
“…As demonstrated by the use of selective EP receptor antagonists, the production of immunosuppressive TGFβ by MDSCs requires the EP 2 receptor or a combination of EP 2 and EP 4 receptors 53,126 . In murine splenic natural killer cells, which express all four PGE 2 receptors, a selective EP 4 agonist inhibited IFNγ production, whereas selective EP 1-3 agonists did not 127 . All of these experiments implicate that elevated cAMP levels are the primary signal leading to immunosuppression, irrespective of which EP receptor is predominant (EP 2 or EP 4 ).…”
Section: Cox2 and Pge 2 Receptorsmentioning
confidence: 87%
“…They can release effect molecules with particle exocytosis to kill target cells, and can also induce apoptosis of target cells through Fas-Fasl death signal transduction pathway (Piconese et al, 2008). NK cells can not only remove malignant cells in the body, but also can play an immune surveillance role in tumorigenesis, directly inhibit tumor cell growth and prevent metastasis of tumor and tiny cancer embolus so that they play a very important role in the body's antitumor immunity (Holt et al, 2011). Therefore, the detected percentages of T cell subsets and NK cells in plasma can represent changes of lymphocytes in circulation and are effective indicators to reflect postoperative cellular immune function in tumor patients and to have important value for determining the prognosis of tumor patients after operations (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%